Investment Contribution as a Driver of the Fisheries Subsector in Eastern Indonesia - Meirinaldi Meirinaldi; Said Latuconsina; Darwati Susilastuti; Widiyarini Widiyarini (CV. Publikasi Indonesia, 2024)
The potential of the fisheries sector in Eastern Indonesia is very large. Investment as a driving force for the fisheries subsector is not only needed for infrastructure, but the fish processing industry sector also requires very large investment. Even though foreign investment is helping to drive this sector, the amount is still not optimal, the main reason is that licensing is long and complicated. Limited investment gives rise to illegal fishing and overfishing which cannot be avoided even though prevention is always carried out in various ways. This research uses a panel data linear regression method to determine the magnitude of the contribution of investment as a driver of the fisheries sector. The result is that investment, employment and the fish processing industry sector can jointly influence the growth of the fisheries sector. Investment in infrastructure development must be followed by investment for the needs of the fish processing industry